The Commandments and Prohibitions Rules of Interpretation in Quranic Exegesis - Kadir, Muhd. Najib Abdul; Usman, Abur Hamdi; Ishak, Hamdi; Ismail , Ashraf; Saad, Mohd Faizulamri Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study seeks to examine the interpretation rules as proposed by M. Quraish Shihab (b. 1944) which centres on the debates of commandments (al-amr) and prohibitions (al-nahy). Shihab in his Quranic work, Tafsir Al-Mishbah had proposed a number of rules that had motivated him towards exegeting the verses. Respected exegetes have also adopted this particular rule to make sure their interpretation are consistent with the Islamic law. Hence, this study has followed the document analysis method by making language scriptures and acclaimed exegeses as the main sources of reference in order to get a proper conclusion, and to make sure the rules that Shihab had used can be examined perfectly. The study established that Shihab had employed some rules associated to al-amr and al-nahy in his methodology, and the rules have been confirmed and also consistent by both scholars and exegetes.